Perception of Library Users on the Use of ICT Facilities in Abia State Polytechnic Library, Nigeria - Wisdom O. Anyim (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study was carried out to determine the perception of library users on the use of ICT facilities in Abia State Polytechnic Library, Nigeria. The study adopted survey research design. The population of the study comprised 4,857 registered users of Abia State Polytechnic library, Nigeria. The convenience sampling technique was used to select a sample of 200 respondents for the study. A structured questionnaire titled “Perception of Library Users on the Use of ICT Facilities in Abia State Polytechnic Library Questionnaire (PLUUSIFASPLIQ)” was used as an instrument for data collection. Data collected for the study was analyzed using frequency counts and percentages to answer research questions. The findings of the study revealed that users are not satisfied with the adequacy of computers, internet and databases facilities in the library. The findings also revealed observable attitude of librarians towards the use of ICT in rendering services which include lack of interest in providing adequate ICT facilities, poor mastery of ICT facilities in rendering services, inadequate knowledge of appropriate ICT facilities, more comfortability with traditional facilities than ICTs, and lack of strong Library and Information Science background of most library staff. Findings also showed that library users need basic ICT facilities in the library for research purposes, preparing for lecture; preparing for exam; updating knowledge and also for printing, photocopying and scanning documents. Finally, it was recommended that the Abia State Polytechnic should make adequate provision of fund to acquire needed ICT facilities in the library; conduct regular training on library-based ICTs and consider ICT skill as one of the major requirements for recruitment in the library.